Message - Islam, Dr. Md. Shahidul (Universal Journal of Pharmaceutical Research, 2020)
We know knowledge multiplies knowledge. The knowledge which we have learned from our teachers, researchers, has been disseminated far and wide through our students and young researchers.UJPR has gone a long way since its inception. Now we have to drive it toward the modern era for the whole professional and continue to make welfare of the world. It should research a standard where it will be considered as an icon for all scientific journals. Actually the UJPR managing team, is very cooperative and helpful, responding punctually and promptly to us, and always sharing with the board every detail. Another important thing, scheduled for publishing maintained by the journal very strongly. UJPR is an International journal that gathers editors and researchers from all over the world. Each published research paper in the journal has been review through several stages to maintain the quality of paper of journal and strictly follow public ethics. Editorial Board members originates from different countries like; India, Bangladesh China, Egypt, Nigeria, Malaysia, Ireland, Indonesia, Hungary, United States, Switzerland, Italy, Spain, Saudi Arabia, Syria, United Kingdom, South Africa, Iraq, and Brazil. National and International level Editorial board member is very active for suggestions and contribution. Authors originated from Nigeria, Egypt, India, China, and many others. Its citation is very good. UJPR is indexed and abstracted in more than 40 well known indexing services including CAS, CASSI (American Chemical Society), DRJI, BASE, Directory of Science, ROAD, ESJI, COSMOS, Academic Keys, etc. many more. It’s my pleasure to inform you that in previous years "Universal Journal of Pharmaceutical Research" have published more than 186 articles of different authors from different countries including Nigeria, Yemen, India, Cameroon, Egypt, China, Pakistan, Iran, Iraq, Malaysia, Sudan, Bangladesh, Saudi Arabia, USA, West Indies, and Nepal.The journal had 184 citations until January, 2020. So, this journal is prestigious and appropriated by many Researchers and Faculty members. I congratulate all the researchers for their contribution in this issue and welcome the eminent and younger for the next issue. A heritage to be carried, a dream to be nurtured, a goal to be succeeded, an era to be generated UJPR is a small step toward that mountain to be climbed.